Prevention of T cell activation by interference of internalized intravenous immunoglobulin (IVIg) with MHC II-dependent native antigen presentation - Aubin, Éric (Clinical immunology (Orlando, Fla.), 2011)
Copyright © 2011 Elsevier Inc. All rights reserved.